Analisis Tingkat Pemahaman Siswa terhadap Lembaga Keuangan Syariah : Studi Kasus di SMA Negeri 1 Tarakan - Alamsa Alamsa; Irawati HM; Nur ‘Aini (Jurnal Ilmiah Manajemen dan Kewirausahaan, 2025)
In the complex era of globalization, understanding Islamic Financial Institutions (LKS) is crucial for the younger generation as the future leaders of the nation. This study aims to analyze the level of understanding among students at SMA Negeri 1 Tarakan regarding LKS, which serves as a fundamental pillar for sustainable Islamic economic growth. This research employs a quantitative approach with a descriptive survey design. Primary data was collected through an online questionnaire filled out by 94 students using random sampling techniques. The instrument consisted of 20 multiple-choice questions measuring four key competencies: Basic Principles of LKS, Islamic Banking Institutions (LKB), Non-Bank Islamic Financial Institutions (LKBB), and LKS Regulations. Scores were analyzed using the Borda method to determine the relative level of understanding based on competency categories. The results indicate that the competency most understood by students was the Basic Principles of LKS, followed by Regulations, LKB, and LKBB. These findings reinforce that a conceptual and normative learning approach to Islamic finance is more effective for students, particularly in the competencies of LKS and Regulations, while operational and applicative aspects—especially those related to LKB and LKBB—remain areas requiring improvement. Practical implications emphasize the need for strategies to strengthen teaching materials in LKBB competencies through project-based approaches or simulations of non-bank Islamic financial institutions. This would provide a more contextual learning experience and enhance students' understanding of the role of LKBB in the financial system, as well as practical skills relevant to the industry.